Evaluasi Penerapan Rekam Medis Elektronik Dengan Pendekatan Metode Technology Acceptance Model (TAM) Di Instalasi Rawat Jalan Rumah Sakit Gunung Maria Tomohon - Suparlan, Monica Sri Rejeki; Patandung, Vina Putri; Rengkung, Yulita; Pongantung, Henny (Jurnal Manajemen dan Administrasi Rumah Sakit Indonesia (MARSI), 2025)
Gunung Maria Hospital Tomohon has implemented Electronic Medical Records (EMR) since 2023. However, technical challenges and user unpreparedness hinder implementation. Evaluation using the Technology Acceptance Model (TAM) is crucial to identify user perceptions. This study aims to assess the relationship between perceived usefulness, ease of use, behavioral intention, and actual use with EMR implementation. A quantitative cross-sectional design was used, involving 70 respondents. Data were analyzed using chi-square tests. The results show significant associations between EMR implementation and all TAM variables. Optimal EMR implementation supports service quality and administrative efficiency. In conclusion, EMR optimization should focus on training, technical support, and managerial policy.